Time - Varying Correlations, Causality, and Volatility Linkages of Indian Commodity and Equity Markets : Evidence from DCC - GARCH - Perumandla, Swamy; Kurisetti, Padma (Indian Journal of Finance, 2018)
This empirical study explored and examined the dynamic conditional correlations, causality, and volatility linkages between the commodity and equity markets in India. In this study, we utilized the DCC-GARCH framework. The symmetric and asymmetric versions of DCC-GARCH, DCC-GJR GARCH, and DCC-EGARCH were used. Our study incorporated the major Indian equity market indices, BSE Sensex and Nifty 50 and commodity market indices, MCX Comdex and Dhaanya. Our results revealed that a mixed portfolio of commodity - equity had low and negative correlations compared to only equity or only commodity portfolios. We deployed the Granger causality test which indicated the short term integration of returns among the markets. We found a bidirectional causal relation between BSE Sensex and Nifty 50 indices. However, we noticed unidirectional causality between MCX Comdex index to Dhaanya index and Dhaanya to Nifty 50 index. The empirical evidence obtained from this study will be useful for the institutional investors, policymakers, investors, and government while framing strategies for portfolio risk diversification and hedging.